2006
DOI: 10.1007/s10552-005-0409-0
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Characteristics of Childhood Hodgkin’s Lymphoma in Greece: A Nationwide Study (Greece)

Abstract: Our results point to infectious agent(s) as playing an etiological role but do not allow discrimination among the delayed establishment of the herd immunity hypothesis, the population mixing hypothesis or that invoking transmission of the agent(s) from the non-human reservoir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
1
14
0
1
Order By: Relevance
“…As expected this rate is higher compared to the average of 7.8 per 1,000,000 childrenyears (95% CI = 6.2-9.5) that has been calculated for HL in a previous study within the same time period [10]. Overall boys with NHL outnumber girls by a factor of 4:1.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…As expected this rate is higher compared to the average of 7.8 per 1,000,000 childrenyears (95% CI = 6.2-9.5) that has been calculated for HL in a previous study within the same time period [10]. Overall boys with NHL outnumber girls by a factor of 4:1.…”
Section: Resultssupporting
confidence: 53%
“…HL among children represents a distinct disease entity with different epidemiological characteristics [2][3][4] in comparison to the same disease among middle-aged persons. Epstein-Barr virus infection [5][6], socioeconomic status [2] and herd immunity development patterns [7], as well as population mixing [8][9][10] have been studied as potential risk factors along with tonsillectomy [11], genetic susceptibility [12], environmental factors [13][14][15], and perinatal exposures [16][17][18]. Several of these studies are small sized and the results are usually inconclusive, due to the rarity of the disease in absolute terms.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies attempting to correlate development of lymphomas with indirect indices of exposure to infections indicating late attainment of herd immunity, such as birth order, sibship size, crowding index, figures on residency changes, and history of exposure to specific infections, have often found inconsistent and contradictory results [2,6,[9][10][11][12][13][14]. In order to evaluate whether newly diagnosed children with lymphomas compared to their controls, present with a more seronegative pattern, we tested seronegativity to a battery of nine common infectious agents.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the meta-analysis (Martin et al, 2005), we added 3 new studies (Altinkaynak et al, 2006;Petridou et al, 2006;Rudant et al, 2011) and 1 study by Bener et al (2008) in 2008 that enlarged the sample size in 2001 (Bener et al, 2001). Notably, the findings from our meta-analysis suggested that there was limited evidence for a significant association between breastfeeding and the risk of childhood Hodgkin lymphoma.…”
Section: Discussionmentioning
confidence: 97%
“…Briefly, 11 potentially relevant articles that concerned the association between breastfeeding and the risk of childhood Hodgkin lymphoma were identified (Davis et al, 1988;Shu et al, 1995;Grufferman et al, 1998;Smulevich et al, 1999;Hardell et al, 2001;UK Childhood Cancer Study Investigators, 2001;Altinkaynak et al, 2006;Petridou et al, 2006;Bener et al, 2008;Rudant et al, 2011). One article was only published in abstract form in 1998 by Grufferman et al (1998).…”
Section: Literature Searchmentioning
confidence: 99%